Perancangan Bangunan Pengolahan Grey Water Dengan Sistem Lahan Basah Buatan Aliran Bawah Permukaan (LBB-AHBP) Skala Kelurahan - Nopi Stiyati Prihatini; Nanang Saiful Anwar; Indah Nirtha; Rijali Noor; Badaruddin Mu’min (Jurnal Pengabdian Pada Masyarakat, 2022)
Guntung Paikat village is one of the villages located in Banjarbaru city of South Kalimantan, Indonesia. According to data from the central statistics agency of Banjarbaru city 2018, the population in 2017 amounted to 9,922 people with a population density of 4,017 inhabitants per square kilometer. Population density can have an impact on the decrease in environmental quality. Based on the Regulation of the Minister of Environment and Forestry year 2016 No. P.68 that any business or activity that produces domestic wastewater must conduct wastewater treatment resulting from such activities. The results of the analysis of existing conditions in the village Guntung paikat domestic wastewater treatment is still not doused, only using septic tanks to dispose of blackwater waste. While greywater waste is disposed of directly into drainage channels or directly flowed into the river. The purpose of this planning and design is to analyze the existing conditions of the planning area, plan and design wastewater treatment units with constructed wetland systems and estimate the necessary cost budget plans. The units planned at wastewater treatment plants with constructed wetland systems are grease trap units, fastening troughs, and constructed wetland. The Cost Budget Plan required in the construction of Constructed Wetland System in block 1 amounted to Rp.94,328,929.73 and in block 2 amounted to Rp.117,863,128.90.